Ibârat Is?t?ilâh?îyah; Suatu Kajian Tarjamah - Baiq Tuhfatul Unsi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
Ibârat Is?t?ilâh?îyah (idiom) is a language units (can be a word, phrase, or sentence) whose meaning can not be "predicted'' from the meaning of lexical elements and grammatical meaning of the units, so it must be understood in context and translated by finding equivalent in the target language. Idiom in Arabic can be formed from the elements isim, deed and letters. Based on these elements that it would appear the forms of idioms. Judging from the construction, idiom can be grouped into three, namely words, phrases and sentences. Because the idiom is really a very crucial issue in translation activity, we should not be reluctant to seek meaning in the dictionary if an expression is a form which undoubtedly true meaning, to avoid the bias of the translation results and confuse others who read it.